Association between numbers of decayed teeth and HbA1c in Japanese patients with type 2 diabetes mellitus. (3rd April 2017) - Yonekura, Satoru; Usui, Masato; Murano, Shunichi
Abstract: Background: Dental caries (DC) are more prevalent in individuals with diabetes than in healthy individuals. However, the association between glycaemic control and DC has not been well characterized in patients with type 2 diabetes mellitus (T2DM). We therefore assessed the association between glycated haemoglobin (HbA1c) serum concentrations and the prevalence of DC in patients with T2DM. Methods: Retrospective analyses of data pertaining to 108 Japanese patients with T2DM hospitalized because of poor or worsened glycaemic control were included. We divided the patients based on HbA1c into two groups: HbA1c level ≥75 mmol/mol (9.0%) as poorly controlled T2DM, and HbA1c level <75 mmol/mol (9.0%) as a control group. We compared the association of lifestyle factors, dental caries, and periodontal health between patients with poorly controlled T2DM and controls. Stepwise multiple regression analyses were performed to evaluate the association between HbA1c, the absolute number of decayed teeth (DT), the sum of decayed, missing, and filled teeth, and the Met Need Index (MNI). Results: DT was higher and MNI was lower in patients with poorly controlled T2DM as compared to that in controls ( P = 0.006 and P = 0.004, respectively). Multiple regression analyses revealed a significant association between HbA1c levels and DT (adjusted β = 0.039, 95% confidence interval [CI], 0.005 to 0.072, P = 0.025) and the MNI (adjusted β = −0.216, 95% CI −0.374 to −0.058, P = 0.008). Conclusions: DT and MNI were associated with HbA1c in T2DM patients.